PENGARUH PENAMBAHAN SARI SEREH DAPUR (CYMBOPOGON CITRATUS) TERHADAP MUTU BAKSO IKAN PATIN (PANGASIUS HYPOTHALAMUS) - Tri Sujianti; Helmi Haris; Fitra Mulia Jaya (Jurnal Ilmiah Pangan Halal, 2020)
Fisball is product of processed fish that done with mixing the fish that has been crushed with tapioca flour and spices,and formed a circle (ball), then boiled. One of fish that suitable for being as ingredient on making fishball is catfish (Pangasius hypothalamus ).But the problems of catfish is stench that cling on and strong enough so it becomes one of the dislike factor of people so need to diversification of processed fish product with adding the lemongrass (Cymbopogon citratus) for reducing that stench. The objective of the research is to study (1) chemical quality values of catfish (Pangasius Hypopthalmus) fishball (2) organoleptic quality of fishball that were treated with the addition of lemongrass extract (Cymbopogon citratus).This research uses Completely Random Design (CRD) with level 1 (one) treatment, experimental method with 4 treatment levels and 3 replications. Treatment of this research is adding the lemongrass extract (Cymbopogon citratus) on catfish (Pangasius hypothalamus) fishball processing with different (B/B) are: 0%, 5%, 10%, 15%, (from water volume for soaking the patin fish fillet). The result of adding the lemongrass extract research is for reducing stench on catfish (Pangasius hypopththalamus) fishball. The best treatment result is P3 (15% of adding the lemongrass extract) is more better than with concentration of adding the other of lemongrass extract (Cymbopogon citratus), with result of organoleptic test, is: aroma 3,60 and texture 3,76. Chemical analysis is: fat level 12,84%.